THE INFLUENCE OF THE TEACHER'S FACTOR ON THE DEVELOPMENT OF STUDENTS' KNOWLEDGE OF FUNDAMENTAL SCIENCES IN THE INSTITUTE OF LIGHT INDUSTRY AND TEXTILEINDUSTRY - Sadullaev Khamidullo Mansurovich (European Science Publishing, 2023)
The article presents the influence of professors and teachers with comprehensive knowledge and skills on students studying in light industry and textile industry institutes.
Keywords: textile industry, quality of education, study experience, tutor, level of psychological-pedagogical preparation, practical skills, independent education.